Dendê Cohort Project: demographic diagnosis and housing conditions of a low income community in Fortaleza, Ceará - Karol Silva de Moura; Olívia Andréa Alencar Costa Bessa; Sharmênia de Araújo Soares Nuto; Henrique Luis do Carmo Sá; Fátima Maria Fernandes Veras; José Ueleres Braga (Universidade de Fortaleza, 2010)
Objectives: To describe the spatial distribution and functions of the buildings, delineate the demographic profile and characterize the family composition in Dedê Community in Fortaleza-Ce. Methods: Phase zero of the longitudinal study, corresponding to the census or registration of the buildings and the resident population, including georeferencing of properties. The registration of the buildings consisted in the characterization of the type and address data. The census of the residents included family composition, their age and sex. Results: After walking throughout the study area, the geographic location of 3,718 buildings was determined and data from 10,892 community residents were collected. Among registered properties, 3,296 (88.7%) are used exclusively for residence. The enrolled population is composed mainly of youngsters and similarly divided according to sex. The average age of residents is 26.3 years, being 25.1 years for men and 27.5 years among women. One in four buildings, in which we found residents, had more than one nuclear family or there were other people living at home, besides the main family nucleus. Conclusion: The properties assessed in this study are predominantly residential. The studied population is mainly young; there is a similar distribution between the sexes.